2014
DOI: 10.1108/lht-06-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

Information cascades in online reading: an empirical investigation of panel data

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…On the one hand, we ignore the effect of online WOM on consumers' purchase decision when analyzing the impact of promotional information from different sources (different social distance). In fact, a vast number of studies have confirmed the important impact of online WOM on online purchase behaviors [16], [27], [40], [41], [42]. On the other hand, Chinese consumers like to share promotion information and talk about their shopping decisions in the Double 11 promotion [59].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…On the one hand, we ignore the effect of online WOM on consumers' purchase decision when analyzing the impact of promotional information from different sources (different social distance). In fact, a vast number of studies have confirmed the important impact of online WOM on online purchase behaviors [16], [27], [40], [41], [42]. On the other hand, Chinese consumers like to share promotion information and talk about their shopping decisions in the Double 11 promotion [59].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…That is, the loyalty was more likely to have formed [35]. However, information technology is constantly innovating, and the incidence of users switching from an information technology to its competitors is rapidly increasing [37][38][39]. Users will be able to switch between different IT products freely, e.g., operating systems, web browsers, office productivity software, and social networking services software.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The behavioural aspect is defined as intention to make repeated purchases, while the attitudinal one refers to continuous preference or favourable attitude toward certain services or a certain product or firm. In spite of situational influences, marketing efforts, and short-term changes in the performance of the product or service, loyalty is relatively stable, that is why loyalty should be an important construct in the study of IT continuance [15][16][17][18][19]. That affective loyalty serves as a significant and consistent predictor of individuals' repurchasing and continuance decisions has been strongly supported by empirical studies [20].…”
Section: The Dual-process Modelmentioning
confidence: 99%